Morbid phenomena. Considerations on the relationship between mass, boss and formation in distraction in the age of selfie - Figueiredo, Clara (International Gramsci Journal, 2025)
In the age of smartphones, how do crowds, leaders and “aestheticization of politics” relate? Historical fascism operated at the service of “passive revolution”, or expectation thereof. Today, we watch, befuddled, as various morbid phenomena are updated. A minority of property owners continues to exploit the subaltern classes’ undeniable need for new social conditions to survive. Representations of mass movements are no longer the facial features of a 20th century leader, but the selfie itself. From the intersection of “aestheticization of politics” and “passive revolution” – understood not only as categories of historical analysis of specific events, but as a program of actions led by the bourgeoisie – this paper aims to analyze the role of photography, selfies and Instagram in containing crowds and handling crises of representativeness. To this end, the visual syntax of Bolsonaro’s rise to power on Instagram is examined as a case study.